New trends in the interaction of the state and civil society in the context of the “Hearing State” - Kalashnikova, Н.П.; Aitmagambetov, Д.Р. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2021)
The authors consider new trends in strengthening interaction between the state and civil society from the position of the concept of a «Hearing state» implemented in Kazakhstan in various spheres of society development relying on foreign experience, political practices of civil society development, modernization processes that it is undergoing. In all advanced countries, the process of deleviafanation has been going on for a long time, when the state begins to give up several power functions and powers, returning them to citizens who independently make managerial decisions. Thus, the modern state demonstrates that it defends the interests of all groups. Expectations of positive changes have sharply increased in society. Decisions taken at the state level concerning the support of civil society institutions contribute to their growth, professionalization of activities, and the formation of a new Social Contract between the government and society. Non-governmental organizations, as well as civil society in general, are forming new trends in intersectoral interaction. The issues of civil society development are very popular, especially if we consider it in the context of the relationship between the non-governmental sector and the State. At the same time, the civil society of Kazakhstan, as well as civil society in the global plan, is a contradictory phenomenon. Conclusions, several recommendations of a recommendatory nature, indicate that the basic principles of the «hearing state» have already brought concrete results and this process will develop, being filled with new content.